Analisis Isi â€œBackground of The Studyâ€ Proposal Penelitian Mahasiswa Bahasa Inggris Pendahuluan KIP UMS Tahun 2014 - Haryanto, Sigit (Universitas Muhammadiyah Surakarta, 2014)
This study is aimed at understanding the approprietness of writing background of the study at proposal of reserach paper that covers (1) flow of writing, (2) problem presented in the background, (3) the purpose of doing the research. Type of this research is qualitative with documentation as data collection. Data are taken from English students research proposal 2014. Data collected are analysed descriptively by using technic componensial analysis, crossing between students works and theories of writing a good background of the study. The results of the study are the students still do not understand yet how the flow of writing background of the study. The students do not present the problems of the research clearly on the background of the study. The students do not explain why conducting the research.